Safety first: The role of trust and school safety in non-suicidal self-injury - Noble, Rick; Sornberger, Michael; Toste, Jessica; Heath, Nancy; McLouth, Rusty (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2011)
Non-suicidal self-injury (NSSI) has become very prominent among adolescents in middle and high school settings. However, little research has evaluated the role of the school environment in the behaviour. This study examined whether indices of school trust and perceived safety were predictive of NSSI behaviour. Results indicate that these variables allow us to more accurately identify participants who engage in NSSI. Students who report being bullied and threatened, and who have less trust in specific members of school staff are more likely to engage in NSSI.